Intuitive intelligence in business (engineering, construction and manufacturing) - Cronje, Hendrik (Henry Stewart Talks, 2019)
Intuitive intelligence, Construction industry, South Africa, Nelson Mandela, Uncertainty and opportunity, Empathy, Cultural differences, Leadership, Collaboration